Pengaruh Kompetensi Dan Persepsi Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Bank BPD Bali Cabang Utama Denpasar - Wulandari, Tri Rahayu; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
ABSTRACT This research is conducted at PT. Bank BPD Bali Denpasar main branch office. The  research objective was to determine the effect of the competence and leadership perception  towards employees performance. The number of sample is 144 is employees, utilizing the stratified random sampling method. The data collection is conducted through observation, interview, questionnaire and literature study.  Analytical technique used is the multiple linear regression. According tho the analytical result, it is deduced that competence and leadership perception both simultaneous and partial affect significantly towards employees performance. From both of  the independent variables used in this research, competence and  leadership perception, it turns out that competence has dominant effect towards employees performance. Keywords : competence, leadership perception, employees performance